Laboratorial tests with transmission line model based on modified Π circuits - Pereira, T. G. [UNESP]; Moreira, A. C. [UNESP]; Prado, A. J. [UNESP]; Ferreira, A. A. [UNESP]; Pissolato Filho, J. (Institute of Electrical and Electronics Engineers (IEEE), 2017)
One way to model the transmission lines is applying cascades of p circuits for representing these systems. In practice, it is impossible to carry out tests in actual lines responsible for transmitting large blocks of electrical power. Thus, a simple physical model can be important for undergraduate students to familiarize themselves with concepts of electromagnetic waves, electrical length, reflection and refraction of waves. A simple physical model transmission line may consist of resistors, inductors and capacitors. So, the objective of this research was to build a simple physical model of transmission line based on a numerical model. The physical model will have multiple p circuit units with an increase of RL branches in parallel. The various units of p circuits represent the distribution of resistance, inductance and capacitance along the line. The RL branches in parallel introduce the influence of the frequency on line parameters.